Nazar Istri Imran sebagai Ekspresi Taqarrub Spiritual Perempuan: Kajian Tafsir Tahlili QS. Āli 'Imrān [3]: 35 - Mulya Rizka; Febri Wardani; Muhammad Ikhwan (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study explores the vow (nadzar) as a concrete expression of a woman's character and faith in forming a Rabbani (divine) family, through an analytical interpretation of Surah Āli 'Imrān, verse 35. In modern times, women's roles within the household are often overlooked or separated from their spiritual essence. Using a library research method combined with a socio-literary (Adabi Ijtima'i) approach, the study reveals that a vow is more than just a traditional promise or a matter of Islamic law (fiqh); it reflects a mother's visionary nature and genuine heart. The findings show that when Hannah dedicated her unborn child as muharraran (consecrated for worship), her sincerity attracted direct blessings from Allah SWT (anbatahā nabātan ḥasanan). As a result, Maryam was raised in a sacred space (mihrab) under the care of Prophet Zakariya. The study concludes that the vow made by Imran's wife is fundamentally an expression of women's spiritual taqarrub (closeness) to Allah—a voluntary act motivated not by legal requirements but by heartfelt spiritual longing. Moreover, women's role in establishing a Rabbani family foundation is realized through ongoing prayer and spiritual hope for the child's righteousness, beginning well before birth.